Organization of Extracurricular Physical Education at School and Its Role in the Physical and Mental Improvement of Students - Orzukulova Saodat (Indonesian Journal of Community and Special Needs Education, 2023)
The purpose of this article is to examine the role of school-based extracurricular initiatives in facilitating immediate and long-term positive impacts on physical activity, healthy behavior, and obesity in children. A critique of the role of various sports-related initiatives that have been developed to address the obesity epidemic currently facing children within the United States is provided, with a specific emphasis on intramural sports as a preferred mechanism to encourage long-term involvement in sport and physically active pursuits. The article presents support for the notion that a physical education curriculum that includes intramurals before, during, and after school can help children learn the skills to enjoy participation in a variety of sports designed to facilitate lifelong active living.